Globalizing Higher Education in India : Brain Drain in Reverse â€“ A Review - Chadha, Bandana; Rai, R. S.; Dugar, Anurag (Prabandhan: Indian Journal of Management, 2016)
India's bold initiative â€œEducate in India," announced in May 2015 to attract international students and make India a quality higher education hub in Asia is closely linked to Prime Minister Modi's other initiatives namely â€œMake in India," â€œDigital India," â€œSkill India," â€œStart-up India," â€œStand-up India,â€ and â€œSwatch Bharatâ€ (clean India), all aimed towards empowering India and making it a global economic superpower. The initiative recognizes the fact that despite being among the world's youngest countries, India will not be able to reap its demographic dividend if its higher education remains in its current dismissal state. India aspires to transition from having the second highest student population leaving its shores to study abroad to becoming a premier educational destination attracting more international students to its shores. The paper reviewed the current status of India in the global higher education sector, recognized the benefits of globalizing higher education, and identified some of the prerequisites required to internationalize. Drawing inspiration from the experience of Asian countries like Singapore, China, Malaysia, Hong Kong, and Taiwan, it is expected to encourage more debate and future research on ways to attract a higher proportion of international students to India. If India is able to provide the capacity and quality required for its expanding young population while also competing globally to attract inbound international students, then the 'Educate in India' initiative will truly complement other initiatives. While the Govt. of India has already embarked on the journey, a lot more needs to be done to â€œliberalize, privatize, and globalizeâ€ higher education in India to attract and retain international students.